Effect of Gliotoxin on Human Polymorphonuclear Neutrophils - D. T. Shah; S. Jackman; J. Engle; B. Larsen (Hindawi Limited, 1998)
Objectives:Candida albicans is known to produce gliotoxin, which has several prominent biological effects, including immunosuppression. interference with host defenses may arise from the effects of this toxin on leukocyte structure and function.